PENGARUH GRATIS ONGKIR DAN ONLINE CUSTOMER REVIEWS TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN FACETOLOGY DI MARKETPLACE SHOPEE - Aulia Purnamasari; Setio Utomo; Saladin Ghalib; Novia Nour Halisa (Smart Business Journal (SBJ), 2026)
This research investigates the partial and joint effects of Free Shipping and Online Customer Reviews on consumers’ purchase decisions regarding Facetology Sunscreen on the Shopee marketplace. The study employed a quantitative approach with an explanatory research design and involved a sample of 96 respondents selected through purposive sampling. Data were collected by distributing questionnaires directly to respondents, and hypothesis testing was carried out using multiple linear regression analysis with the assistance of SPSS version 25.0. The findings indicate that Free Shipping has a significant partial influence on purchase decisions for Facetology Sunscreen on Shopee. Similarly, Online Customer Reviews show a significant partial effect on consumers’ purchase decisions. Furthermore, both Free Shipping and Online Customer Reviews simultaneously exert a significant and moderately strong influence on purchase decisions for Facetology Sunscreen on the Shopee marketplace.